Identifying mechanisms of tropical cyclone generated orographic precipitation with Doppler radar and rain gauge observations - Lin-Wen Cheng; Cheng-Ku Yu; Syuan-Ping Chen (npj Climate and Atmospheric Science)
Abstract The tropical cyclone (TC) generated orographic precipitation frequently causes severe floods and landslides over coastal and land areas, but its underlying processes remain largely unresolved. This study explored this issue using a high-density rain gauge network and Doppler radar observations to investigate an intense orographic precipitation event over Da-Tun Mountain (DT) in northern Taiwan associated with Typhoon Meari (2011). Detailed examination of observations and the quantification of precipitation enhancement showed that the seeder–feeder mechanism, rather than the widely known upslope lifting mechanism, was a primary contributor to heavy precipitation. Smaller-scale, landfalling convective elements embedded within TC background precipitation and their interactions with DT also influenced the degree of orographic enhancement of precipitation. These rapidly evolving scenarios represent a secondary contributor to the modulation of precipitation intensities. The results from the study provide important insights into the relative importance of the different processes of orographically enhanced precipitation for TCs.